MANAGEMENT OF CYSTOLITHIASIS IN DOMESTIC CATS - Ni Kadek Deasy Pitriyawati; Putu Devi Jayanti; Putu Gede Yudhi Arjentinia (Buletin Veteriner Udayana, 2024)
Cystolithiasis is a disorder of the urinary system which specifically occurs in the urinary bladder due to the formation of an abnormal amount of calculi. The case cat is a domestic cat named Mochi, female, tricolor hair, 2 years old and weighing 2.5 kg. The owner reported that 6 months ago the cat had experienced hematuria and had been given treatment. However, since 2 weeks ago the cat has been seen experiencing dysuria and sometimes experiencing oliguria and hematuria. Supporting examinations carried out include laboratory examinations, namely hematology, ultrasonography (USG), urinalysis. The blood test results showed that the cat had thrombocytopenia. On ultrasound examination, there was no thickening of the urinary bladder wall and a hyperechoic mass. Urinalysis results showed an increase in leukocytes, the presence of blood and protein, and microscopic examination showed the presence of struvite crystals. The cat was diagnosed with cystolithiasis with a fausta prognosis. The therapy given is in the form of fluid therapy, catheter installation, and administration of oral medication in the form of the antibiotic Amoxiclav at a dose of 62.5 mg/kgBW administered twice a day orally for seven days, administration of the herbal medicine Fufang 2 ml once a day and Kejibeling 1/2 Oral capsules twice a day for seven days. The case cat showed good results after treatment for seven days, which was characterized by smooth urination, no indications of hematuria, oliguria and dysuria.